Assessment and reliability analysis of Celtic Manor Hotel Bridge, UK. Issue 4 (26th December 2020) - Wright, Matthew; Jones, Darren; Sibert, Ben
Abstract : The Celtic Manor Hotel Bridge crosses the M4 motorway and forms the main access to the largest hotel and leisure resort in Wales. It was also to be the access for the construction of the Wales International Convention Centre (WICC). A load-carrying assessment found the bridge to be unable to carry a 40 t assessment live load in accordance with Highways Agency, UK guidance BD 21/01, with critical sections failing in shear under its own factored self-weight. A BD 79 risk-management approach using reliability analysis techniques combined with load mitigation interim measures was used to assess the bridge's continued satisfactory performance in the short term. This project uncovered valuable research that provides information on reliability analysis techniques and probability density functions which enabled the application of the technique to this bridge assessment. Strengthening works were designed to enable the bridge to remain in service in the longer term while maintaining safety levels. Shear strengthening was installed during night-time bridge and M4 lane closures and allowed for continued hotel use and passage of construction vehicles without causing any delays to the WICC construction.